2021
DOI: 10.1002/osp4.541
|View full text |Cite
|
Sign up to set email alerts
|

Human adipose tissue gene expression of solute carrier family 19 member 3 (SLC19A3); relation to obesity and weight‐loss

Abstract: Objective: Adipose tissue is a specialized endocrine organ that is involved in modulating whole-body energy homeostasis and expresses a specific subset of genes, which may play a role in adipose tissue metabolism. The aim of this study was to search for novel adipose tissue-specific genes using a tissue panel of RNAseq expression profiles.Methods: RNAseq expression profiles from 53 human tissues were downloaded from the GTex database. SLC19A3 expression was analyzed by microarray or realtime PCR in two sets of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…S1a-b). An RNAseq-based screen identified ThTr2 as adipose tissue-specific; its highest expression in this tissue dominantly correlated with the expression of mitochondrial genes pointing to a possible link between the presence of ThTr2 and brown/beige adipocytes (Pereira et al, 2021). Analysis of RNAseq data of Perdikari et al (2018) reveals that ThTr2 expression is higher than ThTr1 expression (estimated by mRNA counts) in both human WAT and BAT obtained by needle biopsies from the neck area (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…S1a-b). An RNAseq-based screen identified ThTr2 as adipose tissue-specific; its highest expression in this tissue dominantly correlated with the expression of mitochondrial genes pointing to a possible link between the presence of ThTr2 and brown/beige adipocytes (Pereira et al, 2021). Analysis of RNAseq data of Perdikari et al (2018) reveals that ThTr2 expression is higher than ThTr1 expression (estimated by mRNA counts) in both human WAT and BAT obtained by needle biopsies from the neck area (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous study revealed that ThTr2 expression was lower in neck fat derived adipocytes isolated from individuals carrying FTO rs1421085 obesity risk alleles CC compared to healthy alleles TT [12]. A recent report demonstrated that SC adipose tissue isolated from individuals with obesity expressed lower ThTr2 as compared to lean individuals and the expression of ThTr2 positively correlated with weight loss [30] suggesting its possible role in augmentation of energy metabolism. Thiamine supplementation prevented obesity and obesity-associated metabolic disorders in OLETF rats [65].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that there were some DEGs that were not shared among IPF networks, but have been proven to play indispensable roles in IPF in recent years. Involvement of highly significant DEGs [131], SLC7A11 [132], CLIC5 [133], VIP (vasoactive intestinal peptide) [134], SMAD6 [135], BMPR2 [136], APOA1 [137], IN-SIG1 [138], TLR3 [139], NLRP12 [140], ADRB1 [141], TLR8 [142], GATA3 [143], CCR2 [144], TLR7 [145], CCRL2 [146], BMPER (BMP binding endothelial regulator) [147], CAV1 [148], TFPI (tissue factor pathway inhibitor) [149], FADS1 [150], SUCNR1 [151], CADM2 [152], SLC19A3 [153], SGCG (sarcoglycan gamma) [154] [177], WNT3A [178], APOH (apolipoprotein H) [179], CHRM3 [180], CD36 [181], TRIB3 [182], PCSK9 [183], ACVR1C [184], GPD1 [123], FFAR4 [185], GPX3 [186], FGF2 [187], FASN (fatty acid synthase) [188], DGAT2 [189], DACH1 [190], PNPLA3 [191], FGF9 [192], SLC7A11 [193], VIP (vasoactive intestinal peptide) [194], KL (klotho)…”
Section: Discussionmentioning
confidence: 99%
“…Signaling pathways include GPCR ligand binding [89], neutrophil degranulation [90], immune system [91], metabolism of lipids [92] and signal transduction [93] made great contribution to the development of IPF. MAP3K15 [94], PRTN3 [95], CX3CR1 [96], AGRP (agouti related neuropeptide) [97], MPO (myeloperoxidase) [98], CD5L [99], S100A8 [100], NPR3 [101], VEGFD (vascular endothelial growth factor D) [102], CXCL11 [103], IL1A [104], CBS (cystathionine beta-synthase) [105], WNT7A [106], SCD (stearoyl-CoA desaturase) [107], LRP2 [108], SLC6A4 [109], BDNF (brain derived neurotrophic factor) [110], CXCL10 [111], ANGPTL7 [112], S100A9 [113], NPY1R [114], IL1B [115], GPIHBP1 [116], CYP1B1 [117], CD36 [118], MACROD2 [119], TRIB3 [120], SPX (spexin hormone) [121], PCSK9 [122], GPD1 [123], CDH13 [124], FFAR4 [125], FGF2 [126], FASN (fatty acid synthase) [127], DGAT2 [128], DACH1 [129], PNPLA3 [130], FGF9 [131], SLC7A11 [132], CLIC5 [133], VIP (vasoactive intestinal peptide) [134], SMAD6 [135], BMPR2 [136], APOA1 [137], INSIG1 [138], TLR3 [139], NLRP12 [140], ADRB1 [141], TLR8 [142], GATA3 [143], CCR2 [144], TLR7 [145], CCRL2 [146], BMPER (BMP binding endothelial regulator) [147], CAV1 [148], TFPI (tissue factor pathway inhibitor) [149], FADS1 [150], SUCNR1 [151], CADM2 [152], SLC19A3 [153], SGCG (sarcoglycan gamma) [154], ADH1B [155], NEGR1 [156], HSD17B12 [157], OXTR (oxytocin receptor) [158] and ANKK1 […”
Section: Discussionmentioning
confidence: 99%